NON-PHARMACOLOGICAL INTERVENTIONS IN HEART FAILURE PATIENTS TO IMPROVE SLEEP QUALITY - Rosiah, Rosiah (Journal of Vocational Nursing, 2022)
Introduction: The Symptoms of Paroxysmal Nocturnal Dyspnea (PND) in patients with heart failure are shortness of breath at night which may appear suddenly causing the patient to wake up and will affect people's quality of sleep. One of the treatments that can be given to patients with poor sleep quality is by providing non-pharmacological interventions. Methods: This study uses a literature review design. The database used in the literature is Google Scholar, Science Direct and PubMed in which the terms are selected and limited with the range 2011-2021 which can be accessed in PDF format. Results: The results obtained five articles of non-pharmacological interventions that can be given to treat the problem of sleep disorders in heart failure patients: massage therapy, position therapy; and Cognitive Behavioral Therapy (CBT). Sleep disorder is not handled properly, it can affect the physical condition of this heart failure patient. Interventions massage therapy are hand, back and foot massage to improve sleep quality in heart failure patients with pain and environmental problems. Heart failure patients, there is a relative change in hemodynamic status so it is necessary to take one of the actions by providing nursing interventions in the form of a right lateral rest position for nursing. Anxiety conditions are one of the mental problems that occur in heart failure patients and CBT interventions can be given. Conclusions: These three therapies are effective in overcoming sleep disturbances and improving sleep quality for heart failure patients.